Bacteriocins Lactobacillus – an alternative to antimicrobial drugs - Voloshina, Iryna; Soloshenko, Kateryna; Krasinko, Victoria; Lych (Tkachenko), Inna; Shkotova, Lyudmila (My University, 2021)
The review presents the characteristics of bacteria of the Lactobacillus family and their ability to synthesize various bacteriocins. The classification of lactobacilli bacteriocins is given, which includes three classes: class I – lantibiotics (peptides with a molecular weight of less than 5 kDa, which containing lanthionine), class II – unmodified bacteriocins, also called non-lantibiotics (heat-resistant peptides, which do not contain lanthionine and have a molecular weight of less 10 kDa) and class III – a poorly studied group of thermolabile proteins with a molecular weight of more than 30 kDa. Lactobacilli are shown to synthesize a wide spectrum of bacteriocins, which demonstrate a variety of actions and are able to inhibit the growth of numerous species of opportunistic gram-positive microflora. The article also provides the examples of lactobacilli bacteriocins isolated from food products (fermented meat, fish, kombucha, goat milk, koumiss, etc.) and various human biotopes (microbiota of breast milk, intestinal tract, and vaginal secretions). Additionally, the review shows the prospects of wide application of bacteriocins synthesized by lactobacilli in the food and pharmaceutical industries.

В огляді наведено літературні дані щодо характеристики бактерій родини Lactobacillus і їх здатності синтезувати різні бактеріоцини. Показана класифікація бактеріоцинів лактобактерій, яка включає три класи: I клас – лантібіотики (містять лантіонін і є пептидами з молекулярної масою менш 5 кДа), II клас – немодифіковані бактеріоцини, які також називаються нелантібіотики (термостійкі пептиди, що не містять лантіоніні мають молекулярну масу менше 10 кДа) і III клас – мало вивчену групу термолабільних білків з молекулярною масою понад 30 кДа. Показано, що Lactobacillus синтезують дуже широкий спектр бактеріоцинів, які володіють різноманіттям дії і здатні інгібувати ріст великої кількості різних видів умовно-патогенної грампозитивної мікрофлори. Також в статті наведені приклади бактеріоцинів лактобактерій, які виділені з харчових продуктів (ферментованого м'яса, риби, чайного гриба, козячого молока, кумису тощо) і різних біотопів людини (мікробіоти материнського молока, кишкового тракту і вагінального секрету). Показана перспективність широкого застосування синтезованих лактобактеріями бактеріоцинів в харчовій і фармацевтичній галузях промисловості.
Keywords: кафедра біотехнології і мікробіології; bacteriocins; Lactobacillus; lactococci; lactic acid bacteria; probiotics; бактеріоцини; лактококи; молочнокислі бактерії; пробіотики